Implementation of Role Playing Model in Social Studies Learning Social Interaction Material for Grade IV Students - Apriani, Lisa; Pandra, Viktor; Lontoh, Willy (Global Education Journal, 2025)
Social Science Education (IPS) is very important to be taught at all levels of formal educational institutions, from elementary school to higher education. The purpose of this study is to examine the implementation of role playing model in social studies learning social interaction material for Grade IV Students of Sukadana Elementary School. The research method used in this study is quantitative with a pseudo-experiment method. The results of the study showed that the average student learning outcome during the pre-test was 49.39 and the student learning completeness reached 9.09% While the average student learning outcome during the post-test was 81.21 and the student learning completeness reached 90.91%, From the comparison it shows that Z_(count)> Z_(table) on the Z distribution list with a significant level of α = 0.05 obtained Z_(count) (5.61) > Z_(table) (1.65) then Ha is accepted and Ho is rejected. So it was concluded that the learning outcomes in social studies learning for grade IV students of SD Negeri Sukadana were significant. This research should be used as a comparative reference in conducting further research and add scientific insights, experience and can contribute to social studies learning, especially improving social studies learning outcomes of students.